TARGETING INFLAMMATION IN ATHEROSCLEROSIS: INSIGHTS FROM NATURAL AND CONVENTIONAL THERAPIES - Vishal Kumar Soni; Prateek Singh; Prashant Kumar Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Atherosclerosis, a cardiovascular disease is known to be one of the major causes of mortality across the globe. It has been predicted that within few years atherosclerosis will be responsible for much greater number of worldwide mortalities. Cardiovascular disease accounts for primary number of all deaths in North America and European countries [1]. Atherosclerosis is derived from the Greek words ‘athero’ meaning paste and ‘sclerosis’ which means hardening. Atherosclerosis is a multifactorial disease characterized by immune-inflammatory processes and lipid deposition in arterial walls, leading to plaque formation and progressive narrowing of blood vessels [2]. This pathology is a major cause of coronary artery disease, myocardial infarction, and stroke. While elevated low-density lipoprotein cholesterol (LDL-C), hypertension, and smoking are established risk factors, emerging contributors such as poor sleep, sedentary lifestyle, microbiome imbalance, environmental pollutants, and psychological stress are increasingly recognized. Together, these factors accelerate plaque growth, vascular dysfunction, and thrombus formation, culminating in severe cardiovascular events. Therapeutic approaches for atherosclerosis target both lipid accumulation and inflammation. Natural compounds like Secoisolariciresinol Diglucoside (SDG), flaxseed lignans, flavonoids (quercetin, anthocyanins), and the medicinal plant Sphaeranthus indicus demonstrate lipid-lowering, antioxidant, and anti-inflammatory effects. Canakinumab, an anti-inflammatory biologic, and Ninjurin1 (NINJ1), a novel immune modulator, show promise as emerging targets. Alongside these, conventional drugs such as nifedipine, ramipril, and perindopril remain critical in managing blood pressure and reducing cardiovascular risk. This review emphasizes the interplay of traditional and non-traditional risk factors in atherosclerosis while outlining both established and innovative therapeutic strategies aimed at reducing disease burden and improving cardiovascular outcomes.